2017
DOI: 10.7150/jca.18743
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Statin Use on Outcomes in Triple Negative Breast Cancer

Abstract: Purpose: We sought to investigate if the use of HMG Co-A reductase inhibitors (statins) has an impact on outcomes among patients with triple negative breast cancer (TNBC). Methods: We reviewed the cases of women with invasive, non-metastatic TNBC, diagnosed 1997-2012. Clinical outcomes were compared based on statin use (defined as ever use during treatment vs. never use). We identified a subset of women for whom a 5-value lipid panel (5VLP) was available, including total cholesterol, low density lipoprotein, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
1
32
1
Order By: Relevance
“…4 ) is in line with the action recently reported of statins inhibiting the YAP-dependent transcription of the pro-metastatic gene RHAMM in these cells 29 31 . Although the concentration of statins used to inhibit YAP nuclear translocation (1 μM) largely exceeds the plasma concentrations of statins used for cardiovascular disease prevention (10 to 200 nM) 32 , statins are the object of intensive studies in cancer recurrence and mortality 33 , 34 . Further work will show whether combined therapy using RA and statins can reverse the malignant phenotype induced by RA in specific breast cancer cells while preserving the anti-tumor effects of retinoids as differentiation enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…4 ) is in line with the action recently reported of statins inhibiting the YAP-dependent transcription of the pro-metastatic gene RHAMM in these cells 29 31 . Although the concentration of statins used to inhibit YAP nuclear translocation (1 μM) largely exceeds the plasma concentrations of statins used for cardiovascular disease prevention (10 to 200 nM) 32 , statins are the object of intensive studies in cancer recurrence and mortality 33 , 34 . Further work will show whether combined therapy using RA and statins can reverse the malignant phenotype induced by RA in specific breast cancer cells while preserving the anti-tumor effects of retinoids as differentiation enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…Ten cohort studies ( 12 , 13 , 15 , 18 20 , 23 , 24 , 26 , 27 ) reported the association between statin use and recurrence of breast cancer. In the original manuscript from Li, the HR results for breast cancer recurrence were reported according to the time of statin use (<3, 3–5, and >5 years) ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although several meta-analyses have been performed to evaluate the association between statin use and prognosis in women with breast cancer ( 29 32 ), only studies published before 2017 were included, and the limited number of studies prevented a comprehensive evaluation of the impacts of study characteristics on the outcomes. Therefore, we aimed to perform an updated meta-analysis regarding the association between statin use and prognosis in breast cancer, by incorporating of the recently published cohorts that were not included in previous meta-analyses ( 17 , 24 28 ). The relative large number of available studies enables us to perform comprehensive analyses regarding the influences of study characteristics on the outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We found 188 preclinical studies references (see Supplementary Material), 18 clinical references [ 10 26 ] and 16 references on clinical trials.gov on drug repurposing for TNBC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence on twelve licensed drugs was found, and of these drugs, eleven out of 268 (4.1%) were included in ReDO_DB. Eleven studies out of 18 were retrospective studies [ 10 13 , 17 , 19 , 20 , 22 , 25 , 26 ], six were phase II and [ 14 16 , 18 , 21 , 23 ] one was a phase I clinical trial [ 24 ] (see Figure 1 for more details). Retrospective studies ranged from 1995 to 2016, and six out of eleven studies analysed a USA cohort of patients [ 10 , 12 , 19 , 20 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%